2007
DOI: 10.1177/0165551506067123
|View full text |Cite
|
Sign up to set email alerts
|

Context representation for web search results

Abstract: Context has long been considered very useful to help the user assess the actual relevance of a document. In Web searching, context can help assess the relevance of a Web page by showing how the page is related to other pages in the same Web site, for example. Such information is very difficult to convey and visualise in a user friendly way. In this paper we present the design, implementation and evaluation of a graphical visualisation tool aimed at helping users to determine the relevance of a Web page by disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Similar results are reported in the study of web search engines. Vegas et al (2007) found that users were more satisfied with search result interfaces that visualise the context of the retrieved web-pages through the use of the DocBall metaphor. Therefore, it appears that context, in the form of an item's position in the hierarchy, can increase the value of the information scent (Pirolli, 2007) communicated to users during the relevance judgment process.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are reported in the study of web search engines. Vegas et al (2007) found that users were more satisfied with search result interfaces that visualise the context of the retrieved web-pages through the use of the DocBall metaphor. Therefore, it appears that context, in the form of an item's position in the hierarchy, can increase the value of the information scent (Pirolli, 2007) communicated to users during the relevance judgment process.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of the topic network and SNA indicators on the WikiMap interface, users can search for relevant nodes around a seed query without spending time clicking forwards and backwards to search for articles. To evaluate the effectiveness of the proposed interface, we conducted two user-oriented search tasks [17][18][19][20]; the first involved searching for a number of items, and the second involved a decision-making task. We discuss the implications of the results below.…”
Section: Discussionmentioning
confidence: 99%
“…A simulated user-oriented search task is designed to evaluate the effectiveness of the proposed interface [17][18][19][20]. The tasks are search missions that need to be accomplished; for example, users may be asked to find articles that are relevant to people in the computer field.…”
Section: Methodsmentioning
confidence: 99%
“…The user can identify through the icon whether the source of the information is a corporate site, a news agency, a product company or a blog. Vegas et al verified that a visualization of an additional level, before the user accesses the result items of the web page level, provides the user with an idea of relevance and delivers promising results in evaluation [41]. The icon is exploited as a component of the surrogates that constitute the result item, providing an assistive visual element.…”
Section: Details On Demandmentioning
confidence: 99%